3D seismic facies recognition based on region growing - Wang, Youtao; Ma, Xiong; Gui, Zhixian; Chen, Xueguo; Wang, Yuelei (Frontiers in Earth Science, 2024)
Seismic facies analysis is an important work for oil and gas exploration. The conventional seismic facies recognition methods are implemented manually with high workload and low accuracy. Therefore, how to obtain seismic facies characteristics quickly, efficiently and accurately is an urgent requirement in seismic facies research.To alleviate this issue, we propose a novel seismic facies recognition method based on the region growing algorithm with the expert knowledge constraint. The processes of this algorithm are as follows: firstly, we select high-density 3D seismic data in the target area for seismic facies identification. Then, we utilize the expert knowledge to define the priori geological constraint for regional growing algorithm. Finally, the region growing algorithm is used to pick up and divide different 3D seismic facies boundaries in the study area. The verification of known geological knowledge proves that the results are reasonable and reliable. The accuracy and efficiency of the proposed seismic facies identification method based on region growing are significantly improved.